Dirty diggers tales from the archaeological trenches - Bahn, Paul G. 1953- (Left Coast Press, 2013)
Fieldwork fun. Incongruous finds ; Everybody hurts sometimes ; Eccentric diggers ; Falling down ; Unpleasant archaeological sights ; Slip-ups -- Excavation encounters. Dealing with the locals ; Men in uniform ; The bear necessities ; More on bones ; The green chair ; Loonies -- Dig dialogues. Intelligent comments ; Stupid questions ; Honest mistakes ; Dishonest mistakes ; Archaeologists are cunning linguists ; Problems with English -- Food and grog and after-effects. Food for thought ; The demon drink ; Don't drink the water! ; Hubble bubble, toilet trouble -- Archaeology after hours. Archaeologists and marriage ; Goings on ; Archaeologists in the raw ; Women and archaeology ; Sex in the field ; The wheeler dealer -- Back at the office. Mummy's boys ; Archaeological theses
Includes bibliographical references (page 123)
Keywords: Archäologie; Archaeology / Anecdotes; Archaeology / Humor; Archaeology / Anecdotes / Humor; Anekdote; Humor